IMPLEMENTATION OF E-PROCUREMENT TO IMPROVE THE QUALITY OF PERFORMANCE AND PUBLIC SERVICES - Irfansyah; Salahuddin; Nirwan (Adisam Publisher, 2024)
E-procurement is an innovation in the government goods/services procurement system whose implementation is carried out electronically based on the web/internet using communication and information technology facilities. In the e-procurement system the entire auction process starting from announcement, submitting bids, selection, to announcing the winner will be carried out online via the internet site. The Indonesian government is currently trying to create a clean government and implement good governance. The principle of implementing Eprocurement is efficiency, which means that the procurement of goods or services uses minimum funds and resources. The goal is to achieve maximum quality. The application of e- procurement in the procurement of government goods/services utilizing internet technology provides many benefits both from the side of the user of goods/services and from the side of the provider of goods and services. From the provider's side, many costs can be saved such as transportation costs. accommodation, and consolidation and document printing costs can be minimized. so that providers can have sufficient space to optimize price reductions for the goods/services they offer.